Analisis Filsafat Stoikisme Pada Tokoh Andy Dufresne dalam Film The Shawshank Redemption - Rosa Lamria Mardiana Simbolon; Syihabuddin Syihabuddin (Journal on Education, 2024)
This research aims to analyze the influence of Stoicism values ​​on the development of moral character, dynamics of social relationships, and acceptance of destiny in the film "The Shawshank Redemption". The research method used is a descriptive qualitative approach, by identifying and describing in depth the Stoicism values ​​reflected in the film narrative. Data were analyzed using content analysis techniques to explore the philosophical and social implications contained in the depiction of stoicism in the film. The research results show that stoicism values, such as loyalty, trust, cooperation, and acceptance of fate, have a significant impact on the moral character that develops in the prison context. The dynamics of social relationships between characters, especially between Andy Dufresne and Red, are reflected as clear evidence of how Stoicism values ​​enrich human interactions in difficult conditions. Acceptance of fate, as the essence of stoicism, is illustrated through the character of Andy, who is able to maintain his composure and even make a positive impact in the harsh prison environment. The results of this research provide in-depth insight into how the philosophy of Stoicism can be applied in everyday life and create positive values ​​amidst difficult life challenges.